(untitled) (Intent Research Scientific Journal, 2023)
The article highlights such issues as the formation of godonyms, theories of linguists on this matter, the fact that godonyms are an important unit at the onomastic level of the language, as well as the toponymic policy pursued in our republic during the years of independence. Think about the morphological and syntactic way of forming godonyms.